Observations on the dynamics of soil, water and biotic communitiesas influenced by Penaeus monodon Fabricius in brackishwater pondsalong Chilka Lake - Mishra, R; Dora, K C (Indian Journal of Fisheries, 2016)
The fringe areas of western sector of the Chilka lagoon which were brought under monoculture of Penaeus monodon wasexamined for the chemical and biological qualities of soil and water to suggest improvement in shrimp yield. In the pondsoils, the pH ranged from 7.86 to 8.25, organic carbon from 0.297 to 0.412%, available nitrogen from 12.88 to19.28 mg 100 g-1 soil and available phosphorus from 3.13 to 4.08 mg100 g-1 soil, indicating nutrient limitations. The total ironcontent ranged from 0.22 to 0.28%. The physico-chemical parameters of the pond water recorded were in the ranges of 8.35- 8.55, dissolved oxygen: 4.42 - 5.11ppm, total alkalinity: 58.4 - 100.8 ppm, salinity: 20.1 - 23.15 ppt, dissolved nitrogen:0.22 - 0.28 ppm and dissolved phosphorus: 0.05 - 0.09 ppm, indicating low nutrient turnover. Poor plankton and benthos isa clear indication of nutrient limitation. The reported moderate yield of shrimp from 148.5 to 212.5 kg ha-1crop-1 suggest apoor fertility status and need for supplementary fertilization.